Optimization of Rheology Parameters for Feedstock by Powder Injection Molding (PIM) Via Taguchi Analysis - Urtekin, Levent; Y?lan, Faik; ?ahin, ?brahim Baki (International Journal of Integrated Engineering, 2023)
The most critical process in the powder injection molding method is determining the powder/binder rate and its properties. The most important feature that distinguishes the powder injection molding method from other powder metallurgy production methods is its advantage in producing high raw density and complex shaped parts. However, providing these advantages includes a multi-parameter process that directly affects the injection molding parameters and the final part's mechanical properties. In addition, the difficulty of experimental studies causes energy, time, and cost losses in determining the powder/binder rate and rheological properties of the feedstock so that the advantages of the method turn into a manageable disadvantage. This study performed rheology studies for three different feedstocks (PW/CW/SA, PW/PE/SA, and PEG8000/PP/SA). In this context, this paper determined the rheological properties of different feedstocks to take advantage of the Taguchi analysis. Flow behavior index, viscosity and optimum loading rates were determined separately for all feedstocks. The results exhibited the injection molding can be done with the determined best (58% steatite+PEG8000/PP/SA) F3 feedstock by volume. Based on it was found that viscosity and melt flow index were not a problem for injection molding in three different feedstocks used in the result, advantages and disadvantages were observed.